Stroke thrombolysis in a middle-income country: A case study exploring the determinants of its implementation - Hwong, Wen Yea; Ng, Sock Wen; Tong, Seng Fah; Ab Rahman, Norazida; Law, Wan Chung; Kaman, Zurainah; Wong, Sing Keat; Puvanarajah, Santhi Datuk; Sivasampu, Sheamini (Frontiers in Neurology, 2022)
Introduction Translation of evidence into clinical practice for use of intravenous thrombolysis in acute stroke care has been slow, especially across low- and middle-income countries. In Malaysia where the average national uptake was poor among the public hospitals in 2018, one hospital intriguingly showed comparable thrombolysis rates to high-income countries. This study aimed to explore and provide in-depth understanding of factors and explanations for the high rates of intravenous stroke thrombolysis in this hospital. Methods This single case study sourced data using a multimethod approach: (1) semi-structured in-depth interviews and focus group discussions, (2) surveys, and (3) review of medical records. The Tailored Implementation of Chronic Diseases (TICD) framework was used as a guide to understand the determinants of implementation. Twenty-nine participants comprising the Hospital Director, neurologists, emergency physicians, radiologists, pharmacists, nurses and medical assistants (MAs) were included. Thematic analyses were conducted inductively before triangulated with quantitative analyses and document reviews. Results Favorable factors contributing to the uptake included: (1) cohesiveness of team members which comprised of positive interprofessional team dynamics, shared personal beliefs and values, and passionate leadership, and (2) facilitative work process through simplification of workflow and understanding the rationale of the sense of urgency. Patient factors was a limiting factor. Almost two third of ischemic stroke patients arrived at the hospital outside the therapeutic window time, attributing patients' delayed presentation as a main barrier to the uptake of intravenous stroke thrombolysis. One other barrier was the availability of resources, although this was innovatively optimized to minimize its impact on the uptake of the therapy. As such, potential in-hospital delays accounted for only 3.8% of patients who missed the opportunity to receive thrombolysis. Conclusions Despite the ongoing challenges, the success in implementing intravenous stroke thrombolysis as standard of care was attributed to the cohesiveness of team members and having facilitative work processes. For countries of similar settings, plans to improve the uptake of intravenous stroke thrombolysis should consider the inclusion of interventions targeting on these modifiable factors.